Social policy, political economy and the social contract - Wistow, Jonathan (Policy Press, 2022)
Positioning social policy within political economy and social contract debates, Wistow draws on empirical evidence to show how the social contract produces longstanding inequitable consequences in relation to health, place and social mobility in England.